Heal Me UMP: A Smartphone-Based Mental Health Screening Application for Nursing Students - Samudra Prihatin Hendra Basuki; Dedy Purwito; Vivi Leona Amelia; Asiandi Asiandi; Gilang Miftakhul Fahmi (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2026)
Mental health disorders, such as depression, anxiety, and stress, significantly affect university students’ academic engagement, particularly among health science students who face demanding academic and clinical workloads. In Indonesia, screening practices remain largely manual, limiting efficiency and timely intervention. This study developed a smartphone-based mental health screening application for nursing students using a Research and Development design with the Four-D model. The resulting Android application, Heal Me UMP, was tested among 129 fifth-semester nursing students. The app offers mental health screening, personalized activity recommendations, and daily reminders. User evaluations demonstrated strong acceptance in terms of usability, usefulness, and system quality (74.5%–78.5%). Content validity was excellent (S-CVI = 1.00), and reliability testing indicated high internal consistency (Cronbach’s alpha = 0.97). These findings suggest that  Heal Me UMP is a feasible, acceptable, and reliable digital tool for early detection of mental health problems among nursing students Keywords: Digital mental health screening, smartphone application, mobile screening,  nursing students, Indonesia